2013
DOI: 10.1007/s10212-013-0191-4
|View full text |Cite
|
Sign up to set email alerts
|

Observed classroom quality in first grade: associations with teacher, classroom, and school characteristics

Abstract: The observation and assessment of quality of teacher-child interactions in elementary school settings are increasingly recognized as important, however research is still very limited in European countries. In this study we examined the quality of the interactions between teacher and children in first grade classrooms in Portugal and the extent to which structural features at teacher-, classroom-, and school-level explained variation in this quality. One hundred and fifteen classrooms participated in the study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…CLASS observers were blind for study condition of the teacher. Studies conducted in the USA (Hamre et al 2007) and various European countries, such Belgium (Buyse et al 2008) and Portugal (Cadima et al 2014), have indicated reliability and validity of various versions of the CLASS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CLASS observers were blind for study condition of the teacher. Studies conducted in the USA (Hamre et al 2007) and various European countries, such Belgium (Buyse et al 2008) and Portugal (Cadima et al 2014), have indicated reliability and validity of various versions of the CLASS.…”
Section: Methodsmentioning
confidence: 99%
“…Second, although the mean weighted kappa scores in this study were similar to those obtained in the Measures of Effective Teaching study (MET study) in the USA (Pianta et al 2012), they still highlight the need for adequate training and coding when using the CLASS. In addition, we used a scoring strategy in line with previous studies (Buyse et al 2008;Cadima et al 2014;Hamre et al 2007). One may however question whether a one-scale-point reliability may have impacted the reliability of the coding system.…”
Section: Limitationsmentioning
confidence: 99%
“…Some studies have also shown that specific school resources (e.g., funds used to support targeted instruction) have an effect on achievement (Archibald, 2006; Lavy, 2012), though such findings are not universally true across the scholarly literature (e.g., Hanushek, 1997, 2003; Houtenville & Conway, 2008). Numerous other studies document the connections between various measures of school quality and outcome measures of student achievement (Berkowitz, Moore, Astor, & Benbenishty, 2017; Cadima, Peixoto, & Leal, 2014; Darling-Hammond, 2000; Kutsyuruba, Klinger, & Hussain, 2015; Lubienski, Lubienski, & Crane, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Teaching Through Interactions framework is also the main theoretical framework referred to in discussing classroom quality in this study. There is a growing body of ongoing research concerning different age groups in different European countries using the teaching Through Interactions framework, and the CLASS measure (e.g., Cadima, Leal, & Burchinal, 2010;Cadima, Peixoto, & Leal, 2014;Pakarinen et al, 2010;Slot, Leseman, Mulder, & Verhagen, 2014;von Suchodoletz et al, 2014), which indicates the importance of understanding process quality also in terms of teacher-child interactions in the broader realm of educational research, as well as indicating the validity of the CLASS measure and the Teaching Through Interactions framework outside the United States. Classroom quality has also been described in terms of child-centred vs teacherdirected practices (e.g., Perry, Donohue, & Weinstein, 2007;Stipek & Byler, 2004).…”
Section: Teachers' Contribution To Classroom Process Qualitymentioning
confidence: 99%